Development of a triazole class of highly potent Porcn inhibitors. Issue 24 (15th December 2016) - You, Lin; Zhang, Chengwei; Yarravarapu, Nageswari; Morlock, Lorraine; Wang, Xiaolei; Zhang, Lishu; Williams, Noelle S.; Lum, Lawrence; Chen, Chuo
Graphical abstract: Abstract: The acyltransferase Porcupine (Porcn) is essential for the secretion of Wnt proteins which contribute to embryonic development, tissue regeneration, and tumorigenesis. We have previously discovered four molecular scaffolds harboring Porcn-inhibitory activity. Comparison of their structures led to the identification of a general scaffold that can be readily assembled by modular synthesis. We report herein the development of a triazole version of this new class of Porcn inhibitors. This study yielded IWP-O1, a Porcn inhibitor with an EC50 value of 80 pM in a cultured cell reporter assay of Wnt signaling. Additionally, IWP-O1 has significantly improved metabolic stability over our previously reported Porcn inhibitors.